The role of cardioenzymes in the diagnostics of infectious heart diseases - I. V. Babachenko; E. V. Sharipova; L. A. Alekseeva; S. N. Chuprova; T. V. Bessonova; Yu. E. Konstantinova (Журнал инфектологии)
Purpose: to evaluate the importance of increasing cardioenzymes in the diagnosis of infectious heart lesions.Object and methods: Under observation were 71 children aged 3 to 17 years (average age – 6.6 ± 0.4 years) who received treatment at the clinic of Pediatric Research and Clinical Center for Infectious Diseases. All children in the acute period of illness and 49 patients with follow-up history were identified with levels of creatine phosphokinase (CPK), MВ fractions of creatine phosphokinase (CPK-MВ), lactate dehydrogenase (LDH), C-reactive protein (CRP), aspartate aminotransferase (AST). Follow-up observation and examination of patients was performed after 1 month and after 1 year. All children were examined for a wide range of pathogens of acute respiratory viral infections, active herpes virus infections (EBV, CMV, HHV-6 type), B19 parvovirus, Chlamydophila pneumoniae, Mycoplasma pneumonia, enteroviruses and bacterial respiratory pathogens. All examined patients underwent electrocardiography and echocardiography.The results of the study. In the examined patients with an increased level of “cardioenzymes” (CPK-MВ, LDH, AST) against the background of acute respiratory infection (ARI), a wide range of diseases was established with damage to both the upper respiratory tract and lower (bronchitis, bronchiolitis, pneumonia), and also other infectious nosologies, including respiratory syndrome (infectious mononucleosis, enterovirus and parvovirus infection). The etiological structure was dominated by a group of herpesvirus (53%) and bacterial infections (25%), as well as their combinations. An analysis of the dynamics of the main biochemical and hematological parameters characterizing the severity of the systemic inflammation syndrome (leukocytes, SRE, CRP, CPK), as well as reflecting myocardial injuries and used in cardiology practice (CPK- MВ, LDH, AST), revealed a long-term (within 1 year observations) the preservation of a moderately elevated level of CPK-MВ, unlike other indicators that returned to normal within 1 month. An increase in CPK-MВ was recorded in 79% of patients with drip infections, while the average level of CPK-MВ in the total sample exceeded the normal values by 1.8-2.4 times.Conclusion. It was found that elevated levels of CPK-MВ and LDH can be used as criteria for the formation of dynamic observation groups and early rehabilitation.